PTH-035 Does Repeat Gastroscopy for Gastric Ulceration Have an Impact On Cancer Detection and Mortality Across Lincolnshire?. (17th August 2016) - Aslam, NS; Ingram, RJM; Mandal, A
Abstract : Introduction: Gastric cancer typically presents late when few options for curative treatment remain. Therefore, emphasis is placed on early detection. Gastric ulceration identified at gastroscopy (OGD) can be a feature of malignancy, which is reported to cause 3% of ulcers (1). Repeat OGD to confirm ulcer healing is recommended within 6–8 weeks by NICE and within 12 weeks as a JAG quality standard. Our aim was to identify the utility of follow-up OGD in the diagnosis of gastric cancer and its impact on patient outcomes at our Trust. Methods: We analysed follow-up OGDs conducted over a 14 month period (21/02/2013 to 28/04/2014) in patients with gastric ulceration identified and reported at index OGD. Endoscopies were performed at three centres (Boston, Grantham and Lincoln). We consulted electronic histology records and the EndoSoft® patient database. Results: 171 patients underwent follow-up endoscopy (45% male, mean age 66 years). Two patients had underlying malignancy at follow-up OGD (gastric adenocarcinoma). Initial biopsies were negative in both. Patient one (44 years, female) was diagnosed by histology. Patient two (69 years, male) had macro- and microscopic evidence of malignancy. Staging for patient one at time of diagnosis was cT3/4 cN0 M1. She underwent explorative laparotomy, which revealed linitis plastica. She received 6 cycles of chemotherapy. The time from diagnosis to death was 436 days Patient two was staged with T3 N2 M0 disease and he underwent a total gastrectomy. Unfortunately an interval CT scan subsequently revealed metastatic spread to the liver. He died 398 days after his diagnosis. Conclusion: Although our cohort was limited in size, malignancy detection rate at repeat OGD was 1.2%. Furthermore, follow-up OGD in this cohort did not impact on 5 year survival. Standardised reporting of gastric ulcer could improve local audit and be useful in JAG assessment of future OGD quality standards. The UK gastroenterology community should also consider whether recommended biopsy protocols should be implemented (2) and whether there is a cohort of our patients for whom repeat OGD can be safely avoided. References: 1 Ingram, et al . PUD Ch 56 Yamada's 6th edition . 2015. 2 Loughrey BM, Johnston BT. Guidance on the effective use of upper gastrointestinal histopathology. Frontline Gastroenterol . 5 (2):88. Disclosure of Interest: None Declared